PENGARUH MODEL PEMBELAJARAN KONTEKSTUAL TERHADAP HASIL BELAJAR SEJARAH SISWA KELAS X MA NW LENEK LAUQ - budiarti, erni; Zidni, Zidni; Saputra, Bambang eka (FAJAR HISTORIA: Jurnal Ilmu Sejarah dan Pendidikan, 2018)
So far there are still many teachers using methods that are not appropriate such as conventional learning models, learning is dominated by teachers. The learning method used tends to be monotonous and teacher-centered. These conditions can also make students passive and the expected learning process will not occur. When the learning process does not occur, learning outcomes will not be obtained as expected. For this reason, we need a method that provides space for students to be able to construct the meaning of the historical events they learned to then be able to connect with their lives. This study aims to determine the effect of contextual learning models on student learning outcomes in historical subjects Class X MA NW Lenek Lauq. This type of research is research using Quasi Experimental Design. The research sample was students of class X MA NW Lenek Lauq. 30 students as experimental class, 30 students as control class. The sample technique used simple random sampling and instruments used multiple choice tests. The analysis requirements test was carried out by Chi-square data normality test, while data analysis was performed with t-test. Based on the results of data analysis, the average value of the experimental group was 78.1 and the control group was 61.1. Then from the results of the hypothesis obtained tcount abel t table is 14,049˃2,002, so that the conclusions in this study are contextual learning models affect the results of history learning at class X MA NW Lenek Lauq in academic year 2018/2019.